Molecular Variability of Crop Pathogens - Carla S. Santos; Marta Nunes da Silva (Crops, 2023)
Crops account for over 80% of the human diet; however, plant diseases and pests are responsible for up to 40% of the loss in food production worldwide, costing approximately EUR 200 billion [...]